2005
DOI: 10.1590/s0100-879x2005000500020
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus seroprevalence and genotypes in patients with diffuse connective tissue diseases and spondyloarthropathies

Abstract: Many extrahepatic manifestations, including rheumatic diseases, have been reported to be associated with hepatitis C virus (HCV) infection. In order to investigate the prevalence of HCV infection among patients with rheumatic diseases, in the present study we interviewed 367 patients and tested their blood samples for HCV antibodies (anti-HCV) by an enzyme-linked immunosorbent assay. Anti-HCV-reactive samples were retested for confirmation by a line immunoassay and also for HCV RNA detection by the polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…In a recent study in our department, HCV antibodies were found in 6.7% among patients with SLE admitted to the rheumatology ward, Cairo University Hospitals, Egypt [6]. This finding indicated that most patients of SLE and associated anti-HCV antibodies were recruited from the outpatient clinic and that the association between HCV infection and SLE does not imply increased SLE disease [12,29,30]. Antibodies to HCV were present in 18/134 Spanish patients with SLE (13%); of them active viremia was detected in 15 SLE patients (11%) [7].These divergences could be attributed to the variability in the prevalence of HCV infection among the different geographic areas and even to different infection control practices in these areas.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study in our department, HCV antibodies were found in 6.7% among patients with SLE admitted to the rheumatology ward, Cairo University Hospitals, Egypt [6]. This finding indicated that most patients of SLE and associated anti-HCV antibodies were recruited from the outpatient clinic and that the association between HCV infection and SLE does not imply increased SLE disease [12,29,30]. Antibodies to HCV were present in 18/134 Spanish patients with SLE (13%); of them active viremia was detected in 15 SLE patients (11%) [7].These divergences could be attributed to the variability in the prevalence of HCV infection among the different geographic areas and even to different infection control practices in these areas.…”
Section: Discussionmentioning
confidence: 91%
“…Such a finding was expected as HCV is a global health threat in Egypt, and the country is the largest reservoir of HCV in the world [19]. Patients with rheumatic diseases have an increased susceptibility to infections including HCV, due to immunosuppression caused by the disease itself and by drugs used in their treatment [42], in addition to their high exposure to numerous invasive diagnostic and therapeutic procedures, including blood transfusions [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Частота коморбидной ВГС инфекции при РА может варьировать в разных популяциях больных, и по данным разных авторов колеблется от 0,65% до 7,6% [59,60]. Наличие вирусного гепатита сущес-твенно повышает риск возникновения побочных реакций при проведении противоревматической терапии.…”
unclassified